2020
DOI: 10.1186/s13059-020-02141-w
|View full text |Cite|
|
Sign up to set email alerts
|

Improved reference genome of the arboviral vector Aedes albopictus

Abstract: Background: The Asian tiger mosquito Aedes albopictus is globally expanding and has become the main vector for human arboviruses in Europe. With limited antiviral drugs and vaccines available, vector control is the primary approach to prevent mosquito-borne diseases. A reliable and accurate DNA sequence of the Ae. albopictus genome is essential to develop new approaches that involve genetic manipulation of mosquitoes. Results: We use long-read sequencing methods and modern scaffolding techniques (PacBio, 10X, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 111 publications
1
123
0
Order By: Relevance
“…The ISV-induced exclusion of flaviviruses has also been observed in an in vitro study where mosquito cells previously infected with PCV were found less permissive to WNV and Murray Valley encephalitis virus (MVEV) [ 38 ]. Besides, the infection of ISV may cause the insertion of viral elements into the mosquito genome and these nonretroviral integrated RNA virus sequences (NIRVs) or endogenous viral elements (EVEs) are known to generate PIWI-Interacting RNAs which might regulate arbovirus replication [ 39 , 40 ]. Instead of competition, sequential exposure of two heterologous arboviruses, CHIKV and ZIKV to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The ISV-induced exclusion of flaviviruses has also been observed in an in vitro study where mosquito cells previously infected with PCV were found less permissive to WNV and Murray Valley encephalitis virus (MVEV) [ 38 ]. Besides, the infection of ISV may cause the insertion of viral elements into the mosquito genome and these nonretroviral integrated RNA virus sequences (NIRVs) or endogenous viral elements (EVEs) are known to generate PIWI-Interacting RNAs which might regulate arbovirus replication [ 39 , 40 ]. Instead of competition, sequential exposure of two heterologous arboviruses, CHIKV and ZIKV to Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Water and eggs/larvae were then collected in sterile 50-ml Falcon tubes and transferred to the insectary of the University of Pavia, Italy. The collected water was divided into three aliquots and used as follows: (i) an aliquot of 200 ml was brought to the ZooPlant laboratory in Milano, Italy, to characterize its microbial composition (samples hereafter called W Start); (ii) 300 ml were aliquoted in two different pans (150 ml/pan) and daily monitored for natural larval hatching in the Pavia insectary (samples named CR); (iii) 600 ml were used to hatch eggs from the Foshan strain ( Chen et al, 2015 ; Palatini et al, 2020 ), after having verified the absence of wild eggs using a stereomicroscope. The Foshan strain is an established laboratory colony derived from wild mosquitoes from South-East China and reared in the Pavia insectary since 2013 ( Palatini et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…All the mosquito genomes used in this study were obtained from VectorBase [ 64 ] and NCBI Assembly [ 65 ] as a result of many studies [ 22 , 25 29 , 43 , 66 72 ]. The GenBank accession codes and other features of the assemblies are listed in S1 Table .…”
Section: Methodsmentioning
confidence: 99%
“…All the mosquito genomes used in this study were obtained from VectorBase [64] and NCBI Assembly [65] as a result of many studies [22,[25][26][27][28][29]43,[66][67][68][69][70][71][72]. The GenBank accession codes and other features of the assemblies are listed in S1 Table. The Mitochondrial DNA (mtDNA) was assembled using the raw reads for some species on Mitobin version 1.9.1 [73].…”
Section: Genomes Analyzedmentioning
confidence: 99%